Mengukuhkan Moderasi Islam untuk Menyelesaikan Terorisme dan Hoax - Alvin Noor Sahab Rizal (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
Islam and Muslims today face at least three challenges; First, the tendency of some Muslims to be extreme and strict in understanding religious laws and try to impose such methods in Muslim communities, even in some cases by using violence. Secondly, other trends that are also extreme by being loose in religion and subject to negative thoughts originating from other cultures and civilizations. Third, the tendency of weak unity among Muslims, they are easily torn apart and easy to bear.In the above three challenges manifested in acts of terror, between groups dropped each other and the rise of hoaxes which have recently been launched by some Muslims, whatever the motives behind it, including enforcing the truth and eradicating kemunkaran, have actually cornered Islam and Muslims in the world. With a different modus operandi, it is necessary for Muslims today to put forward moderation (tawassuth) as a manifestation of ummatan wasathan.